EFFECT OF FOLIAR APPLICATION OF MICRONUTRIENTS ON GROWTH AND FLOWERING OF ROSE CV. TOP SECRET UNDER POLYHOUSE CONDITION - HENAXI PATEL; DIPAL BHATT; S. L. CHAWLA, G. D. PATEL , (The Bioscan, 2016)
An experiment was carried out to study the effect of foliar application of micronutrients on growth and flowering of rose cv. Top Secret under polyhouse condition at green house complex, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari during the year 2013-2014. The experiment was laid out with eighteen treatment combinations with spraying of ZnSO4 (0, 0.2 and 0.4 %) and FeSO4 (0, 0.2 and 0.4 %) at 15 and 30 days interval. The results indicated that the vegetative growth in term of plant height (60.00 cm), number of leaves per stalk (6.78) and leaf area (44.53 cm2) were found significantly superior in foliar application of 0.4 % FeSO4 followed by 0.4 % ZnSO4. The flowering attributes like days taken to flower bud initiation (17.60 days) and days taken to opening of flower bud (19.46 days) was found minimum in foliar application of 0.2 % ZnSO4. Foliar spray of 0.4 % ZnSO4 increased the flower quality parameters like stalk length (56.23 cm), stalk girth (8.88 mm), length of bud (36.2 mm), diameter of flower (9.11 cm), fresh weight of flower stalk (15.81 g), number of petals per flower (34.5), weight of petals per flower (8.66 g) and vase life (9.47 days). The production of flower respectively, number of flower per plant (30.1 and 30.2) and number of flower per square meter (165.7 and 166.5) increased with the foliar spray of 0.4 % ZnSO4 and 0.4 % FeSO4.